Peran Pendidikan Pancasila Dalam Menangkal Radikalisme Di Kalangan Mahasiswa - Denisa Amelia Dwi Kurniawan; Mirnawati Mirnawati; Fahira Fahira; Maura Tasya Salsabila; Sitti Naima; Jusriani Jusriani (Contemporary Education Review, 2025)
This study aims to explore the perceptions of new students in the Accounting Education Study Program, Faculty of Economics and Business, Makassar State University, regarding the role of Pancasila Education in countering radicalism in higher education. This research stems from the understanding that radicalism is not only manifested in the form of violence, but also through intolerance, exclusivism, and ideological narratives that develop in the digital space. Using a descriptive qualitative approach and semi-structured interview method, this study analyzes students' understanding, attitudes, and expectations of Pancasila values. The results show that the majority of students have a good understanding of the basic values of Pancasila and recognize its relevance as an ideological foundation in maintaining national unity amid the challenges of globalization and the flow of digital information. Pancasila education is perceived as playing an important role in shaping students' characters to be tolerant, critical, and inclusive. However, the effectiveness of learning still faces obstacles, mainly due to teaching methods that tend to be theoretical and lack contextual relevance to students' social realities. This study emphasizes the importance of pedagogical innovation in Pancasila Education through the strengthening of dialogue-based learning, contextual case studies, and the use of digital media. This approach is expected to enhance the internalization of Pancasila values in a more reflective and applicable manner, so that Pancasila Education can function optimally as an ideological bulwark against radicalism among the younger generation.